2018
DOI: 10.1111/jar.12534
|View full text |Cite
|
Sign up to set email alerts
|

A review of the frequency and nature of adaptations to cognitive behavioural therapy for adults with Intellectual Disabilities

Abstract: Background There is increasing evidence that cognitive behavioural therapy (CBT) can be effective for people with intellectual disabilities. The aim of this review was to report the nature and frequency of adaptations reported in studies of CBT for people with intellectual disabilities. Method This review updated and extended a previous review by (Whitehouse et al. 2006, J Appl Res Intellect Disabil, 19, 55), which used a framework of adaptations developed by (Hurley et al., 1998, J Dev Phys Disabil, 10, 365).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…The adaptations made to therapy for people with ID in the studies reviewed were consistent with most of the categories of adaptation identified in previous research Whitehouse, Tudway, Look, & Kroese, 2006). None of the adaptations in the studies reviewed appeared to fall in the categories of 'transference/countertransference' or 'disability/rehabilitation approaches', which was also reported by Surley and Dagnan (2019) in their review of adaptations of CBT for people with ID. However, they reported that the use of 'directive methods' was one of the most frequently reported interventions, in contrast to the current review where this was not apparent in any study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The adaptations made to therapy for people with ID in the studies reviewed were consistent with most of the categories of adaptation identified in previous research Whitehouse, Tudway, Look, & Kroese, 2006). None of the adaptations in the studies reviewed appeared to fall in the categories of 'transference/countertransference' or 'disability/rehabilitation approaches', which was also reported by Surley and Dagnan (2019) in their review of adaptations of CBT for people with ID. However, they reported that the use of 'directive methods' was one of the most frequently reported interventions, in contrast to the current review where this was not apparent in any study.…”
Section: Discussionsupporting
confidence: 81%
“…With this factor seemingly playing such a fundamental part in the emotional difficulties of people with ID, it raises the question of whether the reporting of research accurately captures this aspect in descriptions of interventions, rather than this issue not being prevalent in documented therapy. The quality of reporting of adaptations in studies of psychological interventions with people with ID has been highlighted consistently as a significant issue Surley & Dagnan, 2019;.…”
Section: Adapting Psychological Therapies For Adults With Idmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it may be necessary to adjust treatment approaches toward anticipating differences in literacy and other education-related aspects of the patients and provide patients from less privileged backgrounds with additional access options to disorder-specific treatments. Although these implications are not entirely different from those proposed for adjusting psychotherapy for patients with intellectual disabilities (89) or for an aging patient population (90, 91) -which is another challenge ED research might soon face -the effort of their implementation will likely outweigh the social and economic costs of additional social disparities in ED treatment.…”
Section: Anticipating Diversity Challengesmentioning
confidence: 96%
“…Strong evidence has shown that cognitive behavioral therapy (CBT) is beneficial for the nonbrain-injured population that has cognitive impairments, such as those with anxiety, depression, or intellectual disabilities [ 12 , 13 ], or for the population with acquired brain injuries, such as those who experienced cerebral vascular accident, anoxia, and neurosurgery [ 14 ]. The mechanisms underpinning these improvements appear to be that CBT helps TBI patients understand how to identify and change disturbing thought patterns that have a negative influence on behavior and emotions through a psychotherapeutic approach [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%